Zoeal stages of Labidochirus anomalus (Balss, 1913) (Decapoda: Anomura: Paguridae) obtained under laboratory conditions - Kornienko, Elena S.; Korn, Olga M. (Zootaxa, 2015)
Zoeal stages of the hermit crab Labidochirus anomalus (Balss, 1913) (Decapoda: Anomura: Paguridae) are described and illustrated from the larvae reared in the laboratory. The development included four zoeal stages following the typical pattern in the Paguridae. Morphological features of the larvae of L. anomalus are compared with those described for the related species L. splendescens (Owen, 1839). The larvae of both species share numerous zoeal characters and are similar as the species of one genus. At the same time, zoeae of L. anomalus have no dorsal carina on the carapace and long posterolateral carapace spines—key features of the larvae of L. splendescens. These zoeal characters considered as generic are not characteristic of only the genus Labidochirus but sporadically occur among Pagurus species. Main characters of zoeal stages allow assignment of both Labidochirus species to the Group A of Pagurus (the typical representative P. bernhardus).